Microalgal diversity assessment of Laguna Lake (Philippines) tributaries using Next-Generation Sequencing for water quality - JOY ANN SANTOS; JULIUS AARON MEJIA; M.A. JOWINA GALARION; PIERANGELI VITAL (Society for Indonesian Biodiversity, 2023)
Abstract. Santos JA, Mejia JA, Galarion MAJ, Vital P. 2023. Microalgal diversity assessment of Laguna Lake (Philippines) tributaries using Next-Generation Sequencing for water quality. Biodiversitas 24: 4636-4644. The species composition and density of microalgae have been successfully used as bioindicators of water quality as they respond quickly to any change in the water chemistry brought about by pollution. Laguna Lake in the Philippines, one of the country's most important hotspots for aquaculture, continues to be threatened by eutrophication, yet its microalgal profile has been understudied. The presence of microalgae, especially those identified to become causative agents of harmful algal blooms in lakes, can cause corresponding health effects in humans and the environment. This study determined microalgal diversity in samples from tributaries of Laguna Lake, Philippines, through 18S rRNA metagenomic sequencing or Next-Generation Sequencing (NGS). Out of the five sampling sites, only two sites passed the NGS quality control pipeline. Chlorella M.Beijerinck, dominated the eukaryotic microbial population in the Alabang-Cupang River sample, which is 95% of the total population. While in the Biñan River sample, relevant species found were Cyclotella scaldensis Muylaert & Sabbe, Teleaulax acuta (Butcher) Hill, Cryptomonas curvata Ehrenb., and Peridiniopsis penardii (Lemmerm.) Bourr. This is the first study to use NGS to detect microalgae in Laguna Lake and warrants further elucidation of the microalgal population through increased sampling efforts in other recreational and livelihood hotspots. Furthermore, the study results open the importance of implementing new schemes for water quality assessments focused on molecular-based approaches.